Improving Nursing Documentation Quality and Nurse Performance through the Implementation of the 3S-Based Nursing Care Guideline and Supervision Nursing Committee at X Hospital East Jakarta - Rahmi Saptarianti; Indasah Indasah; Agusta Dian Elliana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Effective nursing documentation and optimal nurse performance are essential pillars of high-quality healthcare services. Despite standardised guidelines being available, incomplete documentation and low compliance rates persist in various hospital settings. This study investigated the impact of implementing the 3S-based Nursing Care Guidelines, comprising standardised nursing diagnoses (SDKI), interventions (SIKI), and outcomes (SLKI), along with structured supervision by the hospital's nursing committee, on improving documentation quality and nurse performance. Employing a true experimental pre-posttest control group design, the research involved 49 nurses allocated into three groups: control, intervention with 3S, and intervention with 3S combined with the supervision nursing committee. Data were collected through observation sheets, document audits, and performance checklists. Statistical analyses using Wilcoxon, Mann-Whitney U, and Kruskal-Wallis tests revealed significant post-intervention improvements (p = 0.000) in both outcome areas. The results affirm that integrating structured care models and active supervision effectively enhances the quality of nursing care delivery.